A review of the potentials, challenges and current status of microalgae biomass applications in industrial wastewater treatment. (December 2017) - Mohd Udaiyappan, Ainil Farhan; Abu Hasan, Hassimi; Takriff, Mohd Sobri; Sheikh Abdullah, Siti Rozaimah
Graphical abstract: Highlights: Current applications of microalgae in treating industrial wastewater. Potential of microalgae biomass for industrial wastewater treatment. Challenges of microalgae biomass applications in treating palm oil mill effluent. End use of microalgae cultivated in industrial wastewater. Abstract: Wastewaters from agro-industrial and industrial sources have significant organic matter contents, and some also contain oil and grease, heavy metals and toxic chemicals. Limits have been set for pollutants, especially wastewaters, entering water bodies. Conventional methods of treatment generally require large inputs of energy, large areas of land, and high operation and maintenance costs. Microalgae biomass offers an alternative treatment approach that removes nutrients and other pollutants, such as heavy metals, nitrogen compounds and harmful chemicals. Microalgae harvested after wastewater treatment can be used as value-added products because the microalgae is rich in carbohydrates, proteins and lipids. This paper presents the types of treatment processes, current application of microalgae and high-value products derived from microalgae used in wastewater treatment processes.